ANALISIS KUALITAS LAYANAN, KEPUASAN KONSUMEN, DAN LOYALITAS KONSUMEN ONLINE SHOP NWE LABEL - Ishmah Muslimah (2021)
One of the fast growing online businesses is the online shop NWE Label, whose business development is highly dependent on the growth rate of consumers who buy products at NWE Label. However, currently there is a problem with NWE Label consumer loyalty, namely the willingness to recommend which is indicated by the decreasing number of product ratings on the Shopee NWE Label account. So that the formulation of the problem in this study is whether service quality and customer satisfaction affect consumer loyalty to the online shop NWE Label. The purpose of this study was to prove and analyze the effect of service quality, customer satisfaction on customer loyalty online shop NWE Label. In this study using quantitative data with a population, namely online shop consumers NWE Label. With a sample of 100 consumers who have shopped at the NWE Label online shop more than once and purposive sampling is the method. The analysis technique uses Partial Least Square (PLS) with SmartPLS 3.0 software. The results showed that the variable service quality and customer satisfaction had a positive and significant effect on the loyalty of online shop consumers at NWE Label. The limitation of this study is the lack of knowledge of respondents about the questionnaire statements so that the results obtained by researchers are biased.